2017
DOI: 10.1159/000458514
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Tissue Oxygenation in Neonates via Resonance Raman Spectroscopy: A Pilot Study

Abstract: Background: The ability to monitor tissue oxygenation in neonates remains a challenge due to limited blood supply and the reliance on invasive procedures. Resonance Raman spectroscopy noninvasively measures tissue oxygenation (RRS-StO2). Peripheral tissue oxygenation using this novel technology has not been described in neonates. Objectives: To examine the relationship between short-term RRS-StO2 measurements and central venous saturation (ScvO2) and pulse oximetry (SpO2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In their study, it was on the bottom of a warmed left foot with data collected for 10 min, whereas in our study, the measurement was done closer to the heart, at a preductal site and for at least three times as long. In Iyengar et al [15] study, the RRS-StO2 in other stable preterm infants receiving various buccal RRS-StO2 respiratory support (74.2%) was very similar to the median value for a mixed population of healthy newborns (75.6%) in our study. Preterm infants receive one or more RBC transfusions during their stay in the neonatal intensive care unit that can be associated with increase in morbidity and mortality [22,23].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In their study, it was on the bottom of a warmed left foot with data collected for 10 min, whereas in our study, the measurement was done closer to the heart, at a preductal site and for at least three times as long. In Iyengar et al [15] study, the RRS-StO2 in other stable preterm infants receiving various buccal RRS-StO2 respiratory support (74.2%) was very similar to the median value for a mixed population of healthy newborns (75.6%) in our study. Preterm infants receive one or more RBC transfusions during their stay in the neonatal intensive care unit that can be associated with increase in morbidity and mortality [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…There are a limited number of studies carried out in healthy adults, and these showed that the average S CV O 2 ranged from 75 to 76.8% [20,21]. In another study in neonates, Iyengar et al [15] found that in full-term infants, the average RRS-StO2 was 88.4% at the buccal site and 52.7% at the plantar surface. The difference between their peripheral measurement and ours may be due to the placement of the probe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tiba et al demonstrated that RRS tracks the central venous Hb oxygenation under hemorrhage in the buccal mucosa of swine better, than NIRS . Iyengar et al used RRS to monitor tissue oxygenation in neonates . Authors of all detailed in vivo RRS‐based studies of blood oxygenation used laser excitation at 405 to 407 nm.…”
Section: Introductionmentioning
confidence: 99%